HUBUNGAN ANTARA LINGKUNGAN KELUARGA DENGAN SIKAP SISWA KELAS V SEKOLAH DASAR NEGERI GENTAN KABUPATEN SLEMAN - Hardiman Hardiman (Universitas PGRI Yogyakarta, 2019)
AbstractThis population research is intended to find out whether there is a relationship between the number of family members; father's education level, mother's education level, and student residence atmosphere with the attitude of the fifth grade students of Gentan State Elementary School, Sleman Regency to the school environment. Based on the analysis, the results of the study are as follows: (1) the correlation of the number of family members obtained by the results of rhitung 0.213 with a significant level of 5% and criticism shows 0.264. Thus there is no significant relationship between the number of family members with student attitudes towards the environment around the school. (2) the correlation of the father's education level was obtained by rcount 0.874 with a significant level between the level of education of the father obtained by rcount 0.874 with a significant level of 5% and criticism showing the number 0.264. Thus there is a significant relationship between the level of education of the father and the attitude of students towards the environment around the school (3) the correlation between the level of education of the mother obtained 0.850 with a significant level of 5% and criticism shows the number 0.624. Thus there is a significant relationship between the level of education of mothers with student attitudes toward the environment 5% and criticism shows a number of 0.624 with a significant level of 5% and criticism shows a number of 0.624. Thus there is a significant relationship between the atmosphere of residence and student attitudes towards the school environment. Relating to the results of research conducted by the school. (4) the correlation of the atmosphere of the student's residence is calculated to be 0,738 with a significant level by drawing conclusions, that (1) the number of family members does not affect students 'attitudes towards the school environment (2) the education level of the father and mother influences students' attitudes towards the school environment and (3) the atmosphere of the residence has a profound effect on student attitudes to the school environment.Keywords: environment, family, student attitudes